Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis in Malaysia: a review article - Sim, Su Tein; Chia, Peck Kee; Chhoa, Keng Hong; Chai, Bin Shen (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
N-methyl-D-aspartate receptor (NMDAR) antibody encephalitis is recognized as an autoimmune encephalitis, which is due to autoantibodies against synaptic NMDAR. This disorder affects individuals aged 23 months to 76 years and has a wide range of presentations. In Malaysia, more than 20 cases have been reported. Timely diagnosis and definitive immunotherapy are vital in optimizing functional recovery and prognosis. However, early diagnosis of the condition is often missed due to low awareness among clinicians in Malaysia. This article gathered the medical literature from Malaysia and highlights the aetio-pathophysiology, clinical presentation and management of the disease.